Neem Seed Collection and Marketing: A Case Study in Jhansi District of Uttar Pradesh - Kareemulla, K.; Singh, Mahesh Pal; Sahu, Mukesh Kumar; Kumar, Kuldeep (Indian Journal of Agroforestry, 2020)
It is estimated that almost half of India’s neem trees are in Uttar Pradesh. A study in Jhansi district of Uttar Pradesh was conducted with the aim of assessing the neem seed collection and marketing pattern. Data from the study villages and mandi centre were collected through personal interviews. The farm level analysis of neem trees indicated that while the total trees per farm increased with the farm size, the tree density declined from about 17 trees ha-1among marginal farms to 2.9 trees ha-1in large farms. Both the land lords and landless collected the neem seeds. The average annual seed collected from each of the trees in the study villages worked out to 4.8 kg. The average annual neem seed collection by the sample farmers was 74.6 kg where as it was 70.2 kg per household in respect of professional neem seed collectors. The annual neem seed collection pooled by the local traders in the two sample villages of the district ranged between 5.17 to 9.75q during the three years. The price spread analysis of neem seed marketing by reckoning the marketing channel viz. seed collectors- village assemblers-block level traders- whole sellers indicated that the seed collectors received 48 percent of the sale price of whole sellers.